FEATURES OF METAPHORIZATION IN A POETIC WORK (on the example of the poetry of A. Akhmatova and M. Tsvetaeva) (Scientific journal of the Fergana State University, 2023)
In the article, referring to the concept of "picture of the world", its relation to the worldview is determined, since these two concepts are very often completely identified within the framework of culture. Since the concept of "picture of the world" is one of the fundamental concepts, it expresses the specifics of a person and his life, relationship with the world, the most important living conditions in it. The article presents a study of metaphorization as a model of the world in the poetic works of A. Akhmatova and M. Tsvetaeva using the example of metaphors for the words “water”, “bird”, “voice”, etc.